Factors Associated with Poor Response to Clozapine in Patients with Treatment-resistant Schizophrenia - Jaison George; Abigail Ruth Gojer; Rajesh Gopalakrishnan; Anju Kuruvilla (Current Medical Issues)
Background: Clozapine (CLZ) is the drug of choice for the management of schizophrenia that does not respond to first-line treatments. 40%–70% of patients on CLZ do not have significant improvement and require augmentation. This study aimed to identify factors associated with inadequate response to CLZ in treatment-resistant patients. Methodology: Seventy-four outpatients with a diagnosis of treatment-resistant schizophrenia on CLZ were included in the study. The Positive and Negative Syndrome Scale (PANSS) and Addenbrooke’s Cognitive Examination (ACE III) were used for assessment of the severity of psychosis and cognitive functioning, respectively. A specific pro forma for documenting sociodemographic and clinical details was also used. Results: Seventeen (22.97%) of the participants were found to have a poor response to CLZ. The majority were male with a mean age of 39.11 years (standard deviation [SD] = 9.63). The mean CLZ level was 625.53 ng/mL (SD = 398.59). The mean total PANSS score was 35.07 (SD = 3.65). Cognitive deficits were identified in 51.4% by the ACE III. Younger age at the onset of illness and poor medication adherence were found to have a significant association with inadequate response to CLZ (P < 0.05). Conclusions: Modifiable factors that contribute to CLZ resistance, such as medication adherence, must be effectively managed. Early identification of patients with an inadequate response to CLZ is essential to institute alternate pharmacological and nonpharmacological strategies that will help improve patient outcomes.